Highly Effective Inhibition of Biofilm Formation by the First Metagenome-Derived AI-2 Quenching Enzyme - Weiland-Bräuer, Nancy; Kisch, Martin J.; Pinnow, Nicole; Liese, Andreas; Schmitz, Ruth A. (Frontiers in Microbiology, 2016)
Bacterial cell-cell communication (quorum sensing, QS) represents a fundamental process crucial for biofilm formation, pathogenicity, and virulence allowing coordinated, concerted actions of bacteria depending on their cell density. With the widespread appearance of antibiotic-resistance of biofilms, there is an increasing need for novel strategies to control harmful biofilms. One attractive and most likely effective approach is to target bacterial communication systems for novel drug design in biotechnological and medical applications. In this study, metagenomic large-insert libraries were constructed and screened for QS interfering activities (quorum quenching, QQ) using recently established reporter strains. Overall, 142 out of 46,400 metagenomic clones were identified to interfere with acyl-homoserine lactones (AHLs), 13 with autoinducer-2 (AI-2). Five cosmid clones with highest simultaneous interfering activities were further analyzed and the respective open reading frames conferring QQ activities identified. Those showed homologies to bacterial oxidoreductases, proteases, amidases and aminotransferases. Evaluating the ability of the respective purified QQ-proteins to prevent biofilm formation of several model systems demonstrated highest inhibitory effects of QQ-2 using the crystal violet biofilm assay. This was confirmed by heterologous expression of the respective QQ proteins in Klebsiella oxytoca M5a1 and monitoring biofilm formation in a continuous flow cell system. Moreover, QQ-2 chemically immobilized to the glass surface of the flow cell effectively inhibited biofilm formation of K. oxytoca as well as clinical K. pneumoniae isolates derived from patients with urinary tract infections. Indications were obtained by molecular and biochemical characterizations that QQ-2 represents an oxidoreductase most likely reducing the signaling molecules AHL and AI-2 to QS-inactive hydroxy-derivatives. Overall, we propose that the identified novel QQ-2 protein efficiently inhibits AI-2 modulated biofilm formation by modifying the signal molecule; and thus appears particularly attractive for medical and biotechnological applications.